DIGITAL TRANSITION FOR ROMANIAN TEXTILE INDUSTRY - AILENI Raluca Maria; RADULESCU Razvan Ion; MARIN Cornel Adrian3 (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork)
This paper presents aspects concerning the e-learning courses for the Romanian textile sector in the context of digital transition. In the framework of the ADDTEX Erasmus+ project, INCDTP developed three interactive lessons covering digital aspects of the textile industry. The proposed courses for digital transition cover aspects related to data acquisition, visualization, and analytics-based descriptive, diagnostic, predictive, prescriptive, augmented, and real-time analytics, including mathematical and business modelling by artificial intelligence. The proposed courses gradually introduce the learner to digital knowledge, starting from basic principles necessary for technicians, graduates, engineers, professionals, managers, and mentors. In order to achieve the objectives of the ADDTEX project, the developed courses and certification tools for different specialization levels cover digital aspects that could support innovation in the development of new products based on mathematical models and business modelling, promotion of entrepreneurship and improving the quality and relevance of employers’ skills. In addition, data visualization of historical data record stored in data warehouse for analysis and data visualization using specific tools (scatter, combo, list or stacked plots) help in quick visualization of the aspects related to performance and improves the business outcomes. The courses related to digital transition are available on the Addtex project website and offer learners certificates for completing the courses after the courses after completing the course modules and the electronic tests assigned to each module.